Novel GLDC Compound Heterozygous Variant Leading to Nonketotic Hyperglycinemia: Case Report and Literature Review - Cao, Yanyan; Meng, Lingzhi; Zhang, Yudong; Jiao, Jiancheng; Pu, Weicong; Ma, Li (Frontiers in Pediatrics, 2021)
Nonketotic hyperglycinemia (NKH) is a lethal autosomal recessive disease resulting from alterations in glycine metabolism, commonly caused by mutations in glycine decarboxylase (GLDC). The symptoms of NKH usually manifest in the neonatal period, and can be categorized into severe NKH and attenuated NKH based on the clinical outcome. To date, only a few NKH cases have been reported in China. We here report a case of a neonate with severe NKH carrying a novel compound heterozygous variant in GLDC. The patient was a 68-hour-old girl who had progressive lethargy, no crying, and poor sucking ability from birth, and was therefore transferred to our department. On admission, the patient was supported by intubation and ventilation and presented with profound coma. Metabolic investigation indicated a markedly increased glycine concentration both in the plasma and cerebrospinal fluid (CSF). Symptomatic treatments were administered, but the patient’s condition did not improve substantially. Whole-exome sequencing identified compound heterozygous mutations (c.1261G>C, p.G421R and c.450 C>G, p.N150K) in GLDC, which were inherited from the mother and the father, respectively. The patient was hospitalized for eight days in our department and died two days after discharge. We further summarize the clinical features, genetic characteristics, administered treatment, and prognosis of previously reported Chinese NKH patients for context. Our results highlight that due to the non-specific clinical phenotypes of NKH and difficulty in obtaining CSF samples, genetic testing is a crucial tool, not only for a diagnosis but also for predicting the clinical outcome and can potentially help to determine the optimal therapeutic strategy.